Investigation Activities of Vitamin D, Interleukin-17A, and Alkaline Phosphatase as Biological Markers in Asthma - James Perdinan Simanjuntak; Siti Sakdiah; Fardiah Tilawati Sitanggang; Eva Ayu Maharani (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Inflammation in asthma occurs due to the activation of various cells that produce proinflammatory cytokines. Corticosteroid treatment can affect bone formation, impacting vitamin D levels and alkaline phosphatase (ALP) enzyme activity. This study aimed to evaluate the decrease in vitamin D and increase in ALP due to inflammatory events characterized by an increase in interleukin-17A (IL-17A). The research design is a case-control design. Thirty-four adults with asthma and 34 healthy controls were monitored for blood through laboratory testing. Comparative and correlation statistics were analyzed using Medcalc ver. 19.0.7. All three laboratory parameters showed significant differences between the asthmatic and control groups (P < 0.05). Each vitamin D and ALP gave a good correlated wellults of the IL-17A examination (r = -0.2950; P = 0.015 and r = 0.2590; P = 0.033). There is no significant correlation between Vitamin D and ALP (r = -0.0483; P = 0.696). Moreover, ALP showed a low sensitivity (32%) in identifying vitamin D deficiency in asthmatic patients.